2023
DOI: 10.36456/jpb.v3i2.7002
|View full text |Cite
|
Sign up to set email alerts
|

Morfologi Kota Malang

Abstract: Menelaah morfologi kota memiliki kelebihan dalam menjelaskan bentuk struktur dan karakteristik sebuah kota dan perubahannya dari waktu ke waktu. Berbagai metode banyak dihasilkan untuk mengidentifikasi morfologi kota namun sering kali menemui kesulitan dalam penyediaan datanya dikarenakan skala kota yang cukup besar. Perkembangan teknologi yang pesat memungkinkan penggunaan alat pengindraan jauh seperti foto satelit cahaya malam membantu mengidentifikasi morfologi kota. Penelitian ini bertujuan untuk mengident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Variations might occur in the utilization of spaces by the individuals residing in the region. For example, Afrianto et al (2023) has conducted research in Malang City using Night Time Light (NTL) remote sensing technology. It has been found that Malang City has a circular urban structure that extends towards the North-east and the North of the city.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Variations might occur in the utilization of spaces by the individuals residing in the region. For example, Afrianto et al (2023) has conducted research in Malang City using Night Time Light (NTL) remote sensing technology. It has been found that Malang City has a circular urban structure that extends towards the North-east and the North of the city.…”
Section: Review Of Literaturementioning
confidence: 99%